2006
DOI: 10.1016/j.jacc.2005.12.073
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Negatively Influences Disease Progression and Prognosis in Aortic Stenosis

Abstract: The present study is the first to report that MS is associated with a faster disease progression and worse outcome in patients with AS. Such findings open new avenues of research and provide a strong impetus for the elaboration of additional prospective studies focusing on this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 61 publications
3
89
1
4
Order By: Relevance
“…This is of considerable interest, since in the Helsinki Aging Study, low BMI was identified as a risk factor for aortic valve calcification (3). On the other hand, the metabolic syndrome has been identified as an independent risk factor of AS progression (54). Regarding the risk factors of AS, traditional risk factors of atherosclerosis, including hypercholesterolemia, also predispose to the development of calcific aortic valve disease (1), raising the idea that atherosclerotic risk factors could serve as possible therapeutic targets in AS.…”
Section: Discussionmentioning
confidence: 99%
“…This is of considerable interest, since in the Helsinki Aging Study, low BMI was identified as a risk factor for aortic valve calcification (3). On the other hand, the metabolic syndrome has been identified as an independent risk factor of AS progression (54). Regarding the risk factors of AS, traditional risk factors of atherosclerosis, including hypercholesterolemia, also predispose to the development of calcific aortic valve disease (1), raising the idea that atherosclerotic risk factors could serve as possible therapeutic targets in AS.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the MetS has also been documented as a risk factor for the development of aortic valve sclerosis and stenosis (39). Patients with features of the MetS had a faster progression of aortic stenosis and experienced more events, defined as aortic valve replacement or death (40), and experienced a twofold greater risk of developing dysfunction of an implanted aortic bioprosthesis (41). …”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Et de fait, Drolet et al ont réussi à causer un RA chez des souris en induisant chez celles-ci un SM au moyen d'une alimentation riche en graisses et en hydrates de carbone très similaire à celle qui prévaut pour les humains dans les pays industrialisés (Figure 1) [7]. Ces résultats obtenus chez l'animal nous ont conduit à réaliser une étude rétrospective sur 105 patients victimes d'un RA, dans laquelle nous avons observé que le SM était présent chez 40 % d'entre eux et que la progression du RA était 2 fois plus rapide chez ces derniers [8] rioration des bioprothèses. Cela ouvre donc de nouvelles perspectives de traitement dont l'effet serait de retarder, voire de bloquer, la dégénérescence des bioprothèses.…”
Section: Effets Sur Les Bioprothèsesunclassified
“…Cela ouvre donc de nouvelles perspectives de traitement dont l'effet serait de retarder, voire de bloquer, la dégénérescence des bioprothèses. Parce qu'elles démontrent que le SM est associé à une progression plus rapide de la maladie valvulaire aortique, les suites pratiques de ces études [7,8,11] sont donc que :…”
Section: Effets Sur Les Bioprothèsesunclassified